A STUDY ON LENGTH-WEIGHT RELATIONSHIP, FOOD AND }FEEDING HABITS OF INDIAN SCAD, DECAPTERUS RUSSELL! (RUPPELL, 1830) ALONG THE NORTHWEST COAST OF INDIA - JAISWAR, A. K.; GEORGE, J. P.; GULATI, D. K.; SWAMY, R. P. (Journal of Indian Fisheries Association, 2015)
Length and weight relationship of Decapterus russelli (Ruppell, 1830) is worked out to beW = 0.00312 L3•00 which Indicates the isometric growth of the fish. Study on food and feedinghabits revealed that the species is carnivorous, pelagic, feeding primarily on small crustaceansand small fish species, viz. Acetes indicus, ostracods, Apogon sp., Leiognathus sp., sciaenids,Netnipterus japonicas, Myctophid sp., Trichiurus sp., Therapon sp., D.russelli and occasionallyon prawns. It is a selective feeder on Aeetes indicus.